2009
DOI: 10.1007/s00535-008-2288-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastric secretions affected by esophageal distention in the rat

Abstract: These results indicate that the vagus nerves are involved in the inhibitory effect of esophageal distension on gastric secretory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For rats, which normally do not have reflux, it has been shown that selective destruction of the gastro-esophageal sphincter and the crural sling of the distal esophagus was significantly associated with reflux (Montedonico, Diez-Pardo et al 1999). Since the vagal nerve also represents the principal motor control of the esophagus in rats (Dong et al 2001; Mard et al 2009), any vagal disruption by a direct or indirect pharmacological effect of a test article might therefore result in weakening of the gastro-esophageal sphincter and subsequent reflux. In the literature, however, such a compound-induced sphincter weakening had not yet been described, but the reason may be the difficulty of assessing such an effect.…”
Section: Dysfunction Of the Gastro-esophageal Sphinctermentioning
confidence: 99%
“…For rats, which normally do not have reflux, it has been shown that selective destruction of the gastro-esophageal sphincter and the crural sling of the distal esophagus was significantly associated with reflux (Montedonico, Diez-Pardo et al 1999). Since the vagal nerve also represents the principal motor control of the esophagus in rats (Dong et al 2001; Mard et al 2009), any vagal disruption by a direct or indirect pharmacological effect of a test article might therefore result in weakening of the gastro-esophageal sphincter and subsequent reflux. In the literature, however, such a compound-induced sphincter weakening had not yet been described, but the reason may be the difficulty of assessing such an effect.…”
Section: Dysfunction Of the Gastro-esophageal Sphinctermentioning
confidence: 99%